Palynostratigraphy, Palaeogeography and Source Rock Evaluation of the Nayband Formation at the Parvadeh area, Central Iran, Iran - M. Ghavidel-Syooki; M. Yousefi; D. Mohnhoff (Journal of Sciences, Islamic Republic of Iran)
The Nayband Formation was measured and sampled in Parvadeh area, southern Tabas city. In this area, this formation has a thickness of 1410 m, dividing into four members, namely Gelkan, Bidestan, Howz-e-sheikh and Howz-e-khan. A total 573 samples were treated for Palynological analysis, and only 120 samples were productive. A total of 57 miospore taxa and 11 plant macrofossil were encountered. Based on stratigraphic distribution of  macrofossil and miospore taxa ten assemblage zones were established throughout the Nayband Formation. The encountered miospore taxa and plant macrofossil suggest Upper Triassic (Norian-Rhaetian) for the Nayband Formation.Rock-Eval data shows the presence of organic matter-rich shales with Type III kerogen. The Nayband Formation in the studied section has experienced high temperature which is confirmed by vitrinite reflectance measurements of 0.9-1.2 %VRr. At this thermal maturity stage, organic-rich shales in the formation have generated liquid hydrocarbons as evidenced by the occurrence of solid bitumen in the respective samples.